1994
DOI: 10.3349/ymj.1994.35.4.429
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sympathetic skin response and digital infrared thermographic imaging in peripheral neuropathy

Abstract: It is well known that the SSR (sympathetic skin response) is to evaluate the function of sudomotor activity and Digital infrared thermal imaging (DITI) is to evaluate the function of vasomotor activity of the sympathetic nerve. To assess the sympathetic nerve impairment in the patients with peripheral neuropathy, the SSRs and DITIs were tested in 35 cases. Twenty-four (68.6%) patients were abnormal on SSR test and twenty-nine (82.9%) patients were abnormal on DITI test. In the relationship between DITI and SSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…It has probably been most investigated for breast cancer [6][7][8][9][10][11][12][13], but growing literature reports its use in a variety of other medical conditions [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. To the best of our knowledge, however, there are only two reports of the use of DITI in skeletal trauma.…”
Section: Introductionmentioning
confidence: 96%
“…It has probably been most investigated for breast cancer [6][7][8][9][10][11][12][13], but growing literature reports its use in a variety of other medical conditions [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. To the best of our knowledge, however, there are only two reports of the use of DITI in skeletal trauma.…”
Section: Introductionmentioning
confidence: 96%
“…Considering that IRT visualizes physiological and functional abnormalities rather than anatomical abnormalities, there is no doubt that compared to other imaging diagnostic methods, IRT is an effective diagnostic method for diseases difficult to diagnose with CT or MRI, such as CRPS, neuropathic pain, headache, and myofascial pain. In fact, for CRPS, it is known to have higher sensitivity compared to MRI or three phase bone scan [5,19], and it is reported that thermography has higher sensitivity in diagnosis of neuropathic pain compared to the sympathetic skin response test [20]. When deciding an abnormality in specific diseases, there are different views on what the 'reference temperature difference' should be according to researcher, and for CRPS, standards such as 0.6℃ [21] and 1.0℃ [22] are used.…”
Section: Utilization Of Irt In Pain Medicinementioning
confidence: 99%
“…These time intervals were chosen to replicate time intervals in previous literature. [31][32][33][34] All thermal images were recorded using Computerized Thermal Imaging Processor systems (TIP, TM Computerized Thermal Imaging Inc., Ogden, UT), and analyzed using TIP Med Software (TIP Med Windows XP, Version 3.0.2). Data were placed into an Excel spreadsheet (Microsoft Office Excel 2007) and analyzed using Statistical Package for the Social Sciences (SPSS) software (Version 16).…”
Section: Peripheral Blood Flow Changes After Massage Therapymentioning
confidence: 99%